The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1097/sap.0b013e31823b67ec
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Secondary Wound Closure After Sternal Wound Infection Following Failed Initial Operative Treatment

Abstract: Female patients after CABG, with large sternal wounds infected with gram-negative bacteria and candida, have an 85% risk of wound dehiscence after flap coverage for sternal wound infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
8
0
4
Order By: Relevance
“…Tekumit et al compared two different internal fixation techniques used in cardiothoracic surgery and reported that the rates of dehiscence are similar between the two methods. Wound dehiscence may be attributed to SSI as discussed by Graf et al and Phan et al who both reported that microbial presence as a contributing factor to wound dehiscence. One could suggest that less than optimal surgical closure and infection when combined could be doubly problematic.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Tekumit et al compared two different internal fixation techniques used in cardiothoracic surgery and reported that the rates of dehiscence are similar between the two methods. Wound dehiscence may be attributed to SSI as discussed by Graf et al and Phan et al who both reported that microbial presence as a contributing factor to wound dehiscence. One could suggest that less than optimal surgical closure and infection when combined could be doubly problematic.…”
Section: Discussionmentioning
confidence: 95%
“…Timely and sustained postoperative wound healing plays a significant role in optimising a patient's postoperative recovery and rehabilitation. It has been established that surgical wound dehiscence (SWD) contributes to increased morbidity and mortality rates, and implicit and explicit costs for individuals and health care providers (1)(2)(3)(4)(5). Explicit costs result from prolonged hospitalisation, the need for community nursing and support services and the use of wound management consumables (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Der M. latissimus dorsi wird aufgrund der verlässlichen Gefäßanatomie und -versorgung als gestielte und freie Lappenplastik seit vielen Jahren im Rahmen vielfältiger plastischer Rekonstruktionen eingesetzt [14,15] Individuelle Patientendaten und perioperative Parameter, die sich in anderen Studien bereits als die Wundheilung beeinflussend herausgestellt haben, wurden registriert, um diese auf einen statistischen Zusammenhang in Hinblick auf Vorkommen der 2 Zielvariablen "revisionspflichtige Wundheilungsstörung" und "revisionspflichtige Nachblutung" hin zu untersuchen. Hierzu zählen allgemeine Patientencharakteristika (Geschlecht, Alter, BMI), Vorerkrankungen (Diabetes mellitus, COPD, Niereninsuffizienz), das Keimspektrum bei Defektdeckung sowie perioperative Parameter (OP-Zeit, Art der perioperativen Antikoagulation) [6,14,[16][17][18][19]. Die Zielvariable "revisionspflichtige Wundheilungsstörung" wurde allgemein formuliert, es handelte sich hierbei um Wundrandnekrosen (z. T. mit partiellem Lappenverlust), die nicht mit konservativer Wundbehandlung therapierbar waren und daher operative Revisionen erforderlich machten.…”
Section: Treatment Of Sternal Osteomyelitis After Median Sternotomy Iunclassified
“…This method together with pectoralis flap coverage decreases the risk of developing sternal dehiscence and therefore is recommended in cases with a history of chest irradiation (1,5). Depending on the localization, extensiveness, and profoundness of the defect a variety of muscle flaps may be used to cover the frontal mediastinum, in particular: pectoralis major, rectus abdominis (VRAM, TRAM) or latissimus dorsi (LD) (11)(12)(13)(14). There are several ways to use them for the individual situations, sometimes in modified fashions, as bipedicle advancement pectoralis flap together with thoracoacromial perforators ("tripedicle") or with greater omental transposition (15,16).…”
mentioning
confidence: 99%